University Students’ Perspectives Towards Using Survey Project Work in English for Science and Technology Courses - Lertkultanon, Suneeporn; Sarobol, Nopporn (LEARN Journal: Language Education and Acquisition Research Network, 2022)
Many benefits of using project work in English language classrooms have been shown in several studies. Students could develop their language skills, collaborative skills, research skills and other skills that they can apply in their future jobs. The aim of this present study is to investigate the benefits that university students gained as well as the difficulties they faced when learning English for Science and Technology courses through survey project work. The participants were 93 undergraduate students from the Faculty of Science and Technology and other faculties studying at a university in Thailand. Both quantitative and qualitative data were collected from a questionnaire and from students’ reflections. The study showed that the students had good attitudes towards learning by doing a survey project. They revealed its benefits in terms of improving language skills, especially speaking skills. The students also agreed that they were more responsible, had developed their learner autonomy, and had improved research skills and other useful skills connecting them to the real world. Regarding their difficulties, they responded that they had problems with time management and lacked collaboration from some team members when doing survey project work. The results of this study could help teachers to employ this method in their classes systematically and successfully.